Designing Student Internship Information System Interfaces Using the Design Thinking Method - Maulana, Jefri Achmad; Putro, Fidi Wincoko; Amri, Arni Muarifah (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
Internship programs are essential for tertiary students to gain relevant experience before entering the workforce. Managing these programs, especially in institutions such as the East Java Province Marine and Fisheries Agency (DKP), poses challenges due to the reliance on paper-based processes and the need for centralized management across 17 branches. Therefore, this research developed a